Innovative Strategies for Institutional Growth of Village-Owned Enterprises (BumDes) in Karawang City - Selvi, Evi; Rahmat Handoko , Zidane; Ekawaty, Novian; Maria, Rina; Nurhasanah, Nunung (Dinasti Publisher, 2024)
Village-Owned Enterprises (BUMDes) are vital economic institutions in rural areas, serving both social and commercial functions. As social entities, BUMDes are expected to prioritize community interests by providing social services. Their primary function is to establish a professional and institutional platform for economic activities while leveraging the village's inherent potential. This approach enhances productivity and effectiveness in local businesses. A recent study aimed to develop a strategy for the institutional development of Village-Owned Enterprises in Karawang City using qualitative research and case study methods. The study found that the development of institutional capacity at both individual and organizational levels was not optimal due to constraints such as limited human resources, budgets, facilities, and infrastructure. Additional challenges included poor inter-sectoral coordination, ineffective implementation of standard operating procedures (SOPs), and deficiencies in understanding, skills, commitment, and leadership within BUMDes. The study recommended diversifying strategies at both individual and organizational levels and forming an Integrated Team Alliance to effectively promote the development of BUMDes in Karawang City.